(untitled) (Baghdad Science Journal, 2009)
A polycrystalline CdSe thin films doped with (5wt%) of Cu was fabricated using vacuum evaporation technique in the substrate temperature range(Ts=RT-250)oC on glass substrates of the thickness(0.8?m). The structure of these films are determined by X-ray diffraction (XRD). The X-ray diffraction studies shows that the structure is polycrystalline with hexagonal structure, and there are strong peaks at the direction (200) at (Ts=RT-150) oC, while at higher substrate temperature(Ts=150-250) oC the structure is single crystal. The optical properties as a function of Ts were studied. The absorption, transmission, and reflection has been studied, The optical energy gap (Eg)increases with increase of substrate temperature from (1.65-1.84)eV due to improvement in the structure. The amorphousity of the films decreases with increasing Ts. The films have direct energy gap and the absorption edge was shift slightly towards smaller wavelength for CdSe:Cu thin film with increase of substrate temperature.it was found that the absorption coefficient was decreased with increasing of substrate temperature due to increases the value of(Eg). The CdSe:Cu films showed absorption coefficient in the range (0.94 x104-0.42x104)cm-1at Ts=RT-250 oC. Also the density of state decreases with increasing of substrate temperatures from (0.20-0.07)eV, it is possibly due to the recrystallization by the heating substrate temperatures.. Also the extinction coefficient, refractive index and dielectric constant have been studied.